An Empirical Study of EFL Writing at Primary School (Volume 9) - Trüb, Ruth (2022)
This book presents a research study investigating young foreign language learners' ability to compose communicative texts in English. It reviews current research on young learners' EFL writing, reports on the learners' EFL writing competence, describes text quality at different CEFR language levels, and discusses current teaching practices and the learners' perception of EFL writing.